Analisis Umur Pakai Oli Pada Fan PLTU Tanjung Enim 3x10 MW - Vernando, Deby; Hendradinata , Hendradinata; Putri, Fenoria; Utami, Ogi Meita; Medi, Ali (MACHINERY Jurnal Teknologi Terapan, 2025)
One of the boiler auxiliaries for the running of the production process is the fan. The fan acts as a primary and secondary air supply and as a vacuum cleaner for the remaining ash when the boiler burns and is discharged into the atmosphere. In this fan often occurs over heat (over heat) one of the causes is the decline in oil quality. Lack of attention to the lubrication system if allowed to continue will experience over heat in the fan which will cause damage to the fan, especially the bearing due to the decrease in oil viscosity caused by operating hours and temperatures that affect the oil in the fan. The data obtained will be processed and analyzed with a Quantitative to see the effect of running hours and temperature on the kinematic viscosity of oil samples. From this study with a test of 40 ° C obtained results at 0 hours (92.88 cSt), 1923 hours (57.94 cSt), 2012 hours (53.26 cSt), 2195 hours (46.82 cSt), 2202 hours (44.75 cSt), 2207 hours (43.26 cSt). From the results of this study, running hours greatly affect the kinematic viscosity value and temperature treatment of oil affects the kinematic viscosity along with the increase in running hours